Global applications of one health practice and care - Yasobant, Sandul 1988-; Saxena, Deepak 1972- (IGI Global, 2019)
"This book emphasizes on various aspects of one health learnings, researcher and practices across the globe. It explores how the one health approach converges all three domains with collaborative efforts of multiple disciplines-working locally, nationally, and globally-to achieve the health for all"...Provided by publisher